2000
DOI: 10.1093/jnen/59.4.308
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinergic Deficit Coincides with Aβ Deposition at the Earliest Histopathologic Stages of Alzheimer Disease

Abstract: Effective therapeutic intervention in Alzheimer disease (AD) will be most effective if it is directed at early events in the pathogenic sequence. The cholinergic deficit may be such an early event. In the present study, the brains of 26 subjects who had no history of cognitive loss and who were in early histopathologic stages of AD (average Braak stage less than II) were examined at autopsy to determine whether a cortical cholinergic decrement was associated with Abeta concentration or deposition. In the super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 136 publications
(65 citation statements)
references
References 41 publications
5
57
0
Order By: Relevance
“…However, the results of one study have suggested that the early neuropathologic stages of AD may be associated with a loss of neocortical choline acetyltransferase activity (39). Conversely, other studies have reported reductions in the number of neurons in the nucleus basalis containing immunoreactivity for TrkA (40) and the lowaffinity p75 neurotrophin receptor (41) in MCI and mild AD.…”
Section: Comparison With Postmortem Studiesmentioning
confidence: 95%
“…However, the results of one study have suggested that the early neuropathologic stages of AD may be associated with a loss of neocortical choline acetyltransferase activity (39). Conversely, other studies have reported reductions in the number of neurons in the nucleus basalis containing immunoreactivity for TrkA (40) and the lowaffinity p75 neurotrophin receptor (41) in MCI and mild AD.…”
Section: Comparison With Postmortem Studiesmentioning
confidence: 95%
“…A␤ peptides are directly neurotoxic by mechanisms involving oxidative stress, mitochondrial dysfunction, apoptosis, and hyperphosphorylation of tau, a microtubule-associated protein that becomes dysfunctional with hyperphosphorylation, causing thereby neurofibrillary tangle formation and abnormal neuronal functions (Behl et al, 1994;Goodman and Mattson, 1994;Busciglio et al, 1995;Meda et al, 1995;Anderson et al, 1996;London et al, 1996;Estus et al, 1997). A␤ also disturbs normal synaptic functions (Davies and Maloney, 1976;Beach et al, 2000) and increases brain susceptibility to injury (Nakagawa et al, 1999(Nakagawa et al, , 2000Lauderback et al, 2001;Koistinaho et al, 2002). In addition to its direct harmful effect on neurons, aggregated A␤ activates microglia and astrocytes (Akiyama et al, 2000) to secrete proinflammatory molecules, reactive oxygen species, and other neurotoxins, causing indirect neurotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…In aging, nondemented humans, there is a statistical association between the depletion of cortical cholinergic markers and measures of A ␤ accumulation [10][11][12] . We have used an immunotoxin to induce cortical cholinergic deafferentation in the rabbit.…”
mentioning
confidence: 99%